Synthetic Pyrophosphorylation Methods and Their Use in Chemical Biology - Yates, Lisa M.; Marmelstein, Alan M.; Fiedler, Dorothea (Synlett, 2014)
The detection and annotation of posttranslationally modified proteins in complex samples has benefited greatly from the ability to chemically synthesize and characterize model compounds harboring the modification of interest. To explore the signaling role of protein pyrophosphorylation, a recently discovered modification mediated by the inositol pyrophosphate messengers, our group has developed a robust method to incorporate pyrophosphate residues into peptide sequences. We highlight several examples from the literature that inspired our chemical approach and discuss future applications of our orthogonal pyrophosphorylation strategy.
Keywords: bioorganic chemistry; pyrophosphorylation; peptides; phosphorimidazolide; phosphorylation; chemoselectivity